Pedagogical Tools of Professional Ideals Management of Modern Student - Zamaletdinov, Radif R.; Kuznetsov, Igor A.; Sakharova, Natalia S.; Gladkikh, Valentina G.; Erofeeva, Natalia E. (International Review of Management and Marketing, 2016)
The urgency of the problem of the study is conditioned by the prevailing trends of the labor market's development, modifying the structure of the professional personality's ideals from the ultimate goal of striving for the standard of professional culture of values to the norms of corporate behavior, in which it is identified more with the particular organization that provides an opportunity to earn, rather than a nominal professional group (teachers, doctors, engineers, etc.). Student's unrealized professional ideals are manifested in their self-alienation from the profession, which is appropriate to the education obtained, and becomes one of the factors increasing the number of "hidden" ones (not working on a specialty) among the unemployed graduates. The established trends in the course of research are responsible for finding ways to solve the urgent problem. In this regard, this paper is focused on the scientific substantiation of pedagogical resources' set of professional ideals' management of modern high school student. The leading method of research of the problem is the simulation method allowing introducing of new discourse of professional culture's values into the semantic content of the professional ideals of students and produce theoretic - methodical substantiation of the established set of pedagogical tools to manage this process. The paper reveals the content of the values of professional ideals (the values of professional culture, professional traditions, choice experience of professional ideal), identifies the destructive features of modern modifications of professional ideal (corporate culture norms), justifies a set of pedagogical professional tools to manage professional ideas (pedagogical system of high school, based on innovative principles of self-organization, partner communication "student - teacher", interdisciplinary nature, self-transformation; innovative pedagogical technologies, focused on the formation of a stable student's self-identity), proves the productivity of the identified set of pedagogical tools in the management of professional ideals (the willingness of students to self-identification; self-organization and self-transformation of professional ideals; creative transfer of professionally significant knowledge on different kinds and scope of activities; inclusion in the different types of creative activities). Paper Submissions can be useful for teachers, researchers, managers, methodologists, post-graduates and university students. Keywords: Professional Ideals, Management, Pedagogical Tools, Corporate Behavior, Professional Culture. JEL Classifications: I21, I25, I28